A legal study of the Section 420 of the Penal Code in regulating internet cheating offences / Nurfetri Sabrina Mohd Sabri - Mohd Sabri, Nurfetri Sabrina (2018)
Internet cheating crimes are no strangers, every year the crime has a high increase with high losses involved. Criminals prefer to use the internet through social media to commit crimes. This method is easier because the victim does not know them and the offender’s identity is unknown to the victim. The victim, easily deceived by internet criminals even though they do not know offender and have never met. Internet cheating cases are investigated by investigating officers under section 420 of the penal code. Unfortunately, Internet cheating cases are difficult to charge in court because they do not have enough evidence to charge the real perpetrator. Normally, investigating officer only charges the third party offender who is account holder. The account holder usually gives their account details to the real perpetrator to be used for internet cheating. However, the prosecution cannot charge the account holder under Section 420 of the Penal Code because lack of evidence. Hence, alternative charge will be used by the prosecutor officer to charge the account holder. Therefore the victim did not get the right defense. Hence, this research is conducted to find out whether Section 420 of the Penal Code is sufficient to prosecute offenders for internet fraudulent offenses. This research was also conducted to look at other statute that could be used in Malaysia for internet cheating, such as the Computer Crimes Act 1997, the Communication and Multimedia Act 1998 or other sections found in the Penal Code such as Section 414 and 411 of the Penal Code. This research also discusses the improvements and recommendation to Section 420 of the Penal Code through the UK Fraud Act 2006 reference or other statutes in Malaysia. As the findings of this research, it shows that Section 420 of the Penal code is not adequate to regulate internet cheating offences because it is very difficult to prove the element of cheating regarding internet cheating offence. Therefore, Section 420 of the Penal Code should be amended or prosecution can use alternative statute which is Computer Crimes Act 1997 which is more flexible to charge the real perpetrator in internet cheating offence.